Vitamin D levels in Greek patients with systemic lupus erythematosus. (January 2022) - Athanassiou, Lambros; Kostoglou-Athanassiou, Ifigenia; Tsakiridis, Pavlos; Devetzi, Eirini; Mavroudi, Maria; Fytas, Pantelis; Koutsilieris, Michael; Athanassiou, Panagiotis
Objectives: Vitamin D deficiency has been observed in autoimmune rheumatic diseases, such as rheumatoid arthritis. The aim was to study vitamin D in patients with systemic lupus erythematosus (SLE) and its relationship with disease activity. Methods: In a cohort of 45 patients with SLE, 41 females and 4 males, aged 47.07 ± 2.17 years (mean ± SEM), and range = 21–79 years, 25(OH)D3 levels were determined by electrochemiluminescence. C3 and C4 levels were also analyzed. SLE disease activity was estimated by SLEDAI-2K. Observations were also performed in a control group matched for age and sex. Results: In this cohort of SLE patients, 25(OH)D3 levels were 40.36 ± 2.41 nmol/L (mean ± SEM) as opposed to 60.98 ± 4.28 nmol/L in the control group ( p < 0.001, Student's t test). Vitamin D levels were related to C3 ( p < 0.001, linear regression analysis), correlation coefficient 0.106, r 2 = 0.011, and C4 ( p < 0.001); correlation coefficient 0.316 and r 2 = 0.100; and inversely related to disease activity ( p < 0.001), correlation coefficient −0.572 and r 2 = 0.327. 25(OH)D3 levels were 17.73 ± 1.20 nmol/L and 12.24 ± 0.93 nmol/L, in the groups without and with renal involvement, respectively ( p = 0.001, Student's t test). Conclusions: Vitamin D levels are low in SLE patients and are inversely related to disease activity. Routine screening for vitamin D levels should be performed in SLE patients.